PENGARUH PENERAPAN BLENDED LEARNING DAN PENGUASAAN TEKNOLOGI INFORMASI GURU TERHADAP MINAT BELAJAR KELOMPOK ILMU PENDIDIKAN AGAMA ISLAM - Lanna Sari Siregar (DIRASATUL IBTIDAIYAH, 2023)
This research is motivated by the interest in learning in the Islamic Religious Education science group of students. In theory, one of the developments in student interest in learning is influenced by factors that come from within the student. Likewise the development of interest in studying the Islamic Religious Education science group expected by teachers at Madrasah Aliyah Negeri (MAN) 1 Panyabungan. This study aims to determine the effect of applying blended learning, mastery of teacher information technology and the influence of both on interest in learning in the Islamic Religious Education study group, then differences in learning outcomes based on the application of blended learning and based on teacher information technology mastery. This type of research is quantitative research using the Ex post facto method. The population in this study were all students of Madrasah Aliyah Negeri (MAN) 1 Panyabungan, totaling 1186 people. The research sample was 119 people. The research results show that there is a correlation between X1 and Y. The value of rcount rtable is 0.993 0.1801 with a significance level of 5%. so that H0 is rejected and Ha is accepted. R2 of 0.98 = 98.7%. The regression equation is Å¶ = 6.676 + 0.998X, the value of Fcount (8602.931) Ftable (3.92), then Ho is rejected and Ha is accepted. It is known that there is a correlation between X2 and Y. The value of rcount rtable is 0.957 0.1801 with a significance level of 5%, so H0 is rejected and Ha is accepted. R2 of 0.916 = 91.6%. The regression equation is Å¶ = 16.346 + 1.104 X, Fcount (1276.217) Ftable (3.92), then Ho is rejected and Ha is accepted. The results of the multiple correlation calculations show that Å¶ = 6.652 + 0.898 X1 + 0.120X2, the value of Fcount (4602.149) Ftable (3.92), then Ho is rejected and Ha is accepted, with a significance value of 5%. R2 = 0.9942 = 0.988 = 98.8%. For the t test and the significance of differences in students' interest in learning based on the application of blended learning obtained tcount 128.977 ttable 1.657. So it can be concluded that Ho is rejected, Ha is accepted. and based on the teacher's mastery of information technology obtained tcount 123.306 ttable 1.657, so it can be concluded that Ho is rejected Ha is accepted. With a significance level of 0.000 0.05.Â Keywords: Application of Blended learning and Mastery of Teacher Information Technology; Interest in Learning